UPAYA SEKOLAH DALAM PEMBENTUKAN PERILAKU KEAGAMAAN SISWA DI SDIT HUSNAYAIN TEMPEL SLEMAN YOGYAKARTA - Muhammad Fatkhan Muallifin (Prodi PGMI STPI Bina Insan Mulia Yogyakarta, 2020)
This research was motivated because it saw the delinquency or bad behavior of young children. For this reason, special attention is needed from educators in schools in shaping their religious behavior. Likewise in SDIT Husnayain, this SDIT has an effort to shape the religious behavior of its students. This study aims to describe and analyze what forms of school efforts in shaping student religious behavior, what are the supporting and inhibiting factors of the school's efforts at SDIT Husnayain Tempel Sleman Yogyakarta. This research is a qualitative study with the background of SDIT Husnayain Tempel Sleman Yogyakarta. Data collection is done by conducting interviews, observations and documentation. This study also uses the data validity method with source and method triangulation. The results of this study indicate two things: (1) School efforts to shape students' religious behavior through the intraculcular curriculum and support programs. (2) Supporting factors in shaping the religious behavior of students at SDIT Husnayain include school factors and factors of school collaboration with student guardians. While the things that become the inhibiting factors include family and community.